Bujang: The Social Representation of Gen Z Masculinity in Bangka - Drianus, Oktarizal; Meitikasari, Diah; Antasari, Rr. Rina; Syafitri, Shilpa Shetty Tri; Nuraisah, Siti (UIN Sunan Kudus, 2025)
Traditional images still dominate the representation of masculinity as a product of patriarchal ideology. This research examines the representation of masculinity among Generation Z in Bangka Island, exploring whether shifts occur or traditional norms persist. Using a social representation approach, the study investigated 178 Gen Z males through open questionnaires and interviews. They are called Bujang, which anchors for social representation of masculinity. Thematic analysis found that, in Gen Z’s perspective, masculinity focuses on Jadi Urang (being true men), and requires three dimensions: prosperity, sociability, and religiosity. Some norms of masculinity have changed, while others still adopt traditional masculinities in certain social configurations. In production relations, representation shows urang bujang ya begawi (men must work). In power relations, urang bujang belajer tanggungjawab (men have responsibility). In emotional relationships, kelaki jangen nanges (men don’t cry). These themes indicate both shifting and persistent elements of traditional masculinity norms.